Association Between Breakfast to Dysmenorrhea Degree on Students SMAN 2 in Banda Aceh, Indonesia - Husnah Husnah (Indonesian Nutrition Association, 2018)
Introduction: Dysmenorrhea is a common problem in women and can affect the quality of life of personal health and decreased status of quality of life. The risk of dysmenorrhea is age, age of menarche, nutritional status, marital status, family history, physical activity and food intake. Breakfast is an energy supplier that is needed in the first hour of activities. The purpose of this study was to know the relationship of breakfast with the degree of dysmenorrhea in high school students of SMAN 2 Banda Aceh, Indonesia. The SMAN 2 school is located in the coastal area where most of the students come from families with the job of fishermen and traders. People in that area often do the activity early with the habit of having breakfast after completing their activities. Students from SMAN 2 generally have breakfast during rest time after studying, this habit can cause problems such as dizziness, weakness, nausea, bloating, decreased concentration which will affect the health of the students.Methods: The design of the study was analytic observational with cross sectional approach. Sampling from 6th to 13th of January 2018 taken by nonprobability sampling with stratified random sampling method, obtained sample of 132 students. Inclusion criteria are all students of SMAN 2 Class X, XI, XII, have a history of dysmenorrhea since menarche, not suffering from chronic disease (DM, Hypertension, Hyperthyroidism, Ovarian Cyst, myoma) secondary dysmenorrhea, not taking NSAID medicines, unmarried, and not routine doing physical activity. Measurement of dysmenorrhea with Visual Analog scale (VAS) and breakfast using Frequency Food Questionnaire (FFQ) with interview technique.Results: The student with age of menarche most at the age of 10 year that is 43 student (32,6%), normal nutrition status 71 student (53,8%). Student who always eat breakfast is 24 students (18,2%), Student who eat breakfast sometimes is 36 students (27,2%) and student who rarely eat breakfast is 41 students (31,1%). The degree of dysmenorrhea is more on mild pain, 60 students (45,5%) unbearable pain 5 students (3,8%) and moderate pain 35 students (26,5%). Statistical analysis with spearman correlation rank with 95% confidence interval (CI) (α < 0.05) obtained p value = 0.022, it means there is a relationship between breakfast with degrees of dysmenorrhea with correlation coefficient r = 0.2 with the strength of a strong relationship.